An Analysis of Conceptual Metaphors in Taylor Swift’s Album The Tortured Poets Department - Nijmal Adawiyah; Sonya Steffy Silitonga; Salsabil Putri Setiawan; Gerardo Ryan Purba; Meisuri Meisuri (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
This research explores the use of conceptual metaphors in Taylor Swift’s album The Tortured Poets Department, focusing on how metaphorical language is used to express emotional depth and personal experiences. Applying Conceptual Metaphor Theory by Lakoff and Johnson (1980), the study classifies metaphorical expressions into three types: structural, orientational, and ontological. Using a descriptive qualitative approach, data were collected from the official lyrics of 16 songs in the album. The analysis shows that conceptual metaphors are employed consistently to depict abstract ideas such as heartbreak, vulnerability, self-perception, and emotional transformation. Structural metaphors are used to map personal experiences through familiar frameworks, orientational metaphors describe emotional states using spatial direction, and ontological metaphors give physical form to intangible feelings. Through metaphor, Swift constructs vivid imagery that allows listeners to relate to complex emotions in a concrete and meaningful way.